SEMANTICS ANALYSIS OF HOMONYM IN MALEFICENT MOVIE SCRIPT - Yoviana, Dwi Ranti (Universitas Sebelas Maret, 2021)
This study aims to determine the types of homonymy and determine the relationship in the 2014 film script Maleficent Season 1. The method in this research is descriptive qualitative using observation and non-participatory methods in collecting data and using informal methods in presenting the result data. Data analysis is based on its relationship with homonymy with reference to semantic analysis. There are several categories found such as complete homonymy type, partial homonymy, word homonym, word form homonym, lexical homonym, and grammatical homonym. However, in this study the researcher focused on data analysis on two broad types, namely homographs and homophones. Based on the results of the study, it can be concluded that homonym is the most dominant type of homophone.